The effect of two therapeutic interventions on balance in children with spastic cerebral palsy: A comparative study - Mostafa S. Ali, PhD; Ahmed S. Awad, PhD; Mohamed I. Elassal, PhD (Journal of Taibah University Medical Sciences, 2019)
الملخص: أهداف البحث: يتضمن التحكم في وضعيات الجسم، التحكم في موضع الجسم في الهواء لتحقيق الثبات والتوجه. يتم تطبيق برنامج الثبات المحوري لتحسين التوازن والسيطرة على الوضع. إحدى طرق تقوية العضلات التي تستخدم بشكل متزايد في مجموعة متنوعة من الحالات السريرية هي اهتزاز الجسم بالكامل. يهدف البحث إلى المقارنة بين تأثير اهتزاز الجسم الكامل وبرنامج الثبات المحوري على التوازن في الأطفال المصابين بالشلل الدماغي التشنجي لمدة ١٢ أسبوعا. طرق البحث: ٧٢ طفلا مصابون بشلل دماغي تشنجي (فالج شقي ومزدوج) من كلا الجنسين (٥-٨ سنوات)، تم اختيارهم من العيادة الخارجية، بكلية العلاج الطبيعي، جامعة القاهرة. وتم تعيين الأطفال عشوائيا إلى مجموعتين (أ) و(ب). تلقت المجموعة (أ) برنامج الثبات المحوري لمدة ٣٠ دقيقة بينما تلقت المجموعة (ب) اهتزاز الجسم الكامل لمدة ١٠ دقائق، ثلاث مرات أسبوعيا لمدة ١٢ أسبوعا لكلا المجموعتين. وتم تقييم التوازن بواسطة نظام بيودكس للتوازن. النتائج: كان هناك تحسن كبير في جميع المتغيرات في كل مجموعة مع مزيد من التحسن لجميع مؤشرات الاستقرار (الأمامي الخلفي، الجانبي الجانبي والعمومي) في المجموعة (ب). كان هناك اختلاف غير مؤثر فى جميع مؤشرات الاستقرارعند مقارنة الأطفال المصابين بالفالج الشقي بالأطفال المصابين بالشلل المزدوج. الاستنتاجات: ينصح بتطبيق الاهتزاز الجسم الكامل وبرنامج الثبات المحوري في برنامج علاج الأطفال المصابين بالشلل الدماغي التشنجي. وأخيرا، كان اهتزاز الجسم الكامل أكثر تحسنا على التوازن من الثبات المحوري في الأطفال الذين يعانون من الشلل الدماغي التشنجي. Abstract: Objectives: Postural control involves controlling the position of the body in space to achieve stability and orientation. Core stability is needed to improve balance and postural control. Whole-body vibration is a unique strategy for muscle strengthening in various clinical situations. This study compared the effects of whole-body vibration and a core stability program on balance in children with spastic cerebral palsy, with an intervention period of 12 weeks. Methods: A total of 72 children with spastic cerebral palsy (hemiplegic and diplegic), of both sexes (age, 5–8 years), were selected from the outpatient clinic of the Faculty of Physical Therapy, Cairo University. The children were randomly assigned to 2 groups. Group A underwent a core stability program for 30 min and group B underwent whole-body vibration training for 10 min, at 3 times a week for 12 weeks for both groups. Balance was assessed using the Biodex Balance System. Results: A significant improvement in all variables (p < 0.05) was observed in each group, with greater improvement of all stability indices (anteroposterior, mediolateral, and overall) in group B. There were non-significant differences in all stability indices between hemiplegic and diplegic children (p > 0.05). Conclusion: Whole-body vibration and core stability exercises are recommended for the treatment of children with spastic cerebral palsy. Whole-body vibration was more effective than the core stability program in improving balance in children with spastic cerebral palsy. الكلمات المفتاحية: التوازن, الشلل الدماغي, الأطفال, الثبات المحورى, اهتزاز الجسم الكامل, Keywords: Balance, Cerebral palsy, Children, Core stability, Whole body vibration